2021
DOI: 10.21037/tcr-21-426
|View full text |Cite
|
Sign up to set email alerts
|

A nomogram combined with radiomics features, albuminuria, and metabolic syndrome to predict the risk of myometrial invasion of bladder cancer

Abstract: Background: To establish a preoperative prediction model of myometrial invasion of bladder cancer (BC) based on the radiomics characteristics of multi-parameter thin-slice enhanced computed tomography (CT) imaging.Methods: Data from 100 patients with BC were analyzed retrospectively. The patients were divided into two groups: muscular invasive BC and non-muscular invasive BC. The tumor region was segmented from enhanced CT images (arterial-and venous-phase calibration maps) of all patients using Slicer-3D soft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Several studies have reported the promising predictive performance of MRI-based radiomics in preoperatively discriminating between NMIBC and MIBC [ [26] , [27] , [28] , [29] ]. Previous studies have shown that radiomics features extracted from CT can also predict muscular infiltration status in bladder cancer, but most of them were either very small sample sizes [ [ 17 , 18 , 30 ]] or lacked independent external validation [ 31 ]. Our study also demonstrated that radiomics signature alone had promising discriminatory performance in preoperative clinical staging of bladder cancer, with AUCs of 0.840 (95 % CI 0.763–0.918) in the internal validation cohort and 0.807 (95 % CI 0.683–0.930) in the internal validation cohort.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have reported the promising predictive performance of MRI-based radiomics in preoperatively discriminating between NMIBC and MIBC [ [26] , [27] , [28] , [29] ]. Previous studies have shown that radiomics features extracted from CT can also predict muscular infiltration status in bladder cancer, but most of them were either very small sample sizes [ [ 17 , 18 , 30 ]] or lacked independent external validation [ 31 ]. Our study also demonstrated that radiomics signature alone had promising discriminatory performance in preoperative clinical staging of bladder cancer, with AUCs of 0.840 (95 % CI 0.763–0.918) in the internal validation cohort and 0.807 (95 % CI 0.683–0.930) in the internal validation cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, radiomics has made great progress in the automatic diagnosis of colorectal tumors, lung masses, breast diseases and some other diseases [ [9] , [10] , [11] , [12] , [13] , [14] ]. The usefulness of CT-based radiomics in differentiating histological variant [ 15 ], tumor grade [ 16 ] and stage [ [ 17 , 18 ]] of bladder tumors has been demonstrated in previous studies, but these studies had some limitations, such as small sample size or no independent external validation set. In addition, deep learning (DL), widely used in image analysis, had the ability to extract deep and complex structures related to specific tasks, which had shown good performance in diagnosis and prognosis prediction for gastric, liver, and renal cancers [ [19] , [20] , [21] ].…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, the present work is the first study to attempt to estimate the probability of AFS in ALLI patients using a newly developed nomogram. Nomogram establishment is considered a feasible and credible approach for developing disease models [ 9 , 28 ]. In previous studies, determining the probability of AFS based on identified risk factors was not possible.…”
Section: Discussionmentioning
confidence: 99%
“…It has become a trend to include clinical risk factors in the prediction model in order to better predict MIS and improve clinical diagnostic performance and application value. These include tumor size ( 15 ), tumor stalk ( 16 ), proteinuria and multiple sclerosis ( 21 ), as well as VI-RADS ( 20 ) and TURBT ( 14 ).The radiomic model incorporating clinical factors performed significantly better than the conventional MRI examination and simply radiomic model in terms of calibration and discrimination. Radiomic-clinical nomogram can be used as a reliable and non-invasive adjunct to differentiate MIBC from NMIBC preoperatively ( 15 ).…”
Section: Discussionmentioning
confidence: 99%